Hyperosmolar expansion medium improves nucleus pulposus cell phenotype. Issue 3 (18th August 2022) - Laagland, Lisanne T.; Bach, Frances C.; Creemers, Laura B.; Le Maitre, Christine L.; Poramba‐Liyanage, Deepani W.; Tryfonidou, Marianna A.
Abstract: Background: Repopulating the degenerated intervertebral disc (IVD) with tissue‐specific nucleus pulposus cells (NPCs) has already been shown to promote regeneration in various species. Yet the applicability of NPCs as cell‐based therapy has been hampered by the low cell numbers that can be extracted from donor IVDs and their potentially limited regenerative capacity due to their degenerated phenotype. To optimize the expansion conditions, we investigated the effects of increasing culture medium osmolarity during expansion on the phenotype of dog NPCs and their ability to produce a healthy extracellular matrix (ECM) in a 3D culture model. Methods: Dog NPCs were expanded in expansion medium with a standard osmolarity of 300 mOsm/L or adjusted to 400 or 500 mOsm/L in both normoxic and hypoxic conditions. Following expansion, NPCs were cultured in a 3D culture model in chondrogenic culture medium with a standard osmolarity. Read‐out parameters included cell proliferaton rate, morphology, phenotype and healthy ECM production. Results: Increasing the expansion medium osmolarity from 300 to 500 mOsm/L resulted in NPCs with a more rounded morphology and a lower cell proliferation rate accompanied by the expression of several healthy NPC and progenitor markers at gene ( KRT18, ACAN, COL2, CD73, CD90 ) and protein (ACAN, PAX1, CD24, TEK, CD73) level. The NPCs expanded at 500 mOsm/L were able to retain most of their phenotypic markers and produce healthy ECM during 3D culture independent of the oxygen level used during expansion. Conclusions: Altogether, our findings show that increasing medium osmolarity during expansion results in an NPC population with improved phenotype, which could enhance the potential of cell‐based therapies for IVD regeneration. Abstract : This study shows that expansion of dog NPCs in higher osmolarity promotes the expression of healthy NPC and progenitor markers at gene and protein level. This population with improved NPC phenotype could have the potential to exert regenerative effects when injected into degenerated IVDs and would therefore be beneficial for cell‐based therapies.